2000
DOI: 10.1055/s-2000-12984
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Amanita muscaria Monosaccharide Transporter, AmMst1

Abstract: Fungal carbohydrate nutrition is an important aspect of ectomycorrhizal symbiosis. At the plant/fungus interface, fungal and root cortical cells compete for monosaccharides, generated from plant‐derived sucrose. Therefore, the kinetic properties of the monosaccharide uptake systems are decisive for the monosaccharide yield of each partner. For the functional characterization of a hexose transporter (AmMst1) of the ectomycorrhizal fungus Amanita muscaria, the entire cDNA was expressed in a Saccharomyces cerevis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 21 publications
1
37
2
Order By: Relevance
“…Wiese et al, 2000), was not successful (data not shown). The fact that functional expression in heterologous systems does not always work for a number of plant monosaccharide transporters is well known (U. Ludewig, pers.…”
Section: Discussionmentioning
confidence: 94%
“…Wiese et al, 2000), was not successful (data not shown). The fact that functional expression in heterologous systems does not always work for a number of plant monosaccharide transporters is well known (U. Ludewig, pers.…”
Section: Discussionmentioning
confidence: 94%
“…Results from both, uncoupling experiments and electrophysiology, demonstrate a proton-substrate symport mechanism for HXT1p. AmMst1, the closest homolog of HXT1p, also seems to operate as a symporter (36 HXT1p are at least to some extent produced in the extrahaustorial matrix, most likely through a combined action of fungal and plant invertases (R.T.V., U. Möll, S. Wirsel, K.M., unpublished data). Fructose, too, would have to be removed efficiently from this compartment.…”
Section: Discussionmentioning
confidence: 97%
“…An alternate manner, or together with such a porter, may be active transport. H ϩ -hexose cotransport by fungi is well known (Sanders, 1988) and such a transporter has been reported in an ectomycorrhizal species (Wiese et al, 2000).…”
Section: Uptake Of Carbon By the Fungusmentioning
confidence: 99%